2023
DOI: 10.1021/acs.cgd.2c01504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation on Single- and Multicomponent Organic Crystalline Materials

Abstract: Exploration of highly ionizing radiation damage to organic materials has mainly been limited to polymers and singlecomponent organic crystals due to their use in coatings and scintillation detection. Additional efforts are needed to create new tunable organic systems with stability in highly ionizing radiation to rationally design novel materials with controllable chemical and physical properties. Cocrystals are a promising class of compounds in this area because of the ability to rationally design bonding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…[35] Impressively, Tori Z. Forbes et al demonstrated that organic cocrystals could reduce structural defects when exposed to gamma radiation, especially in terms of maintaining crystallinity, stability, and physical properties, compared to polymers and single organic crystals. [36] However, the fundamental mechanism underlying the performance of organic cocrystals when exposed to radiation, the guiding principles for selecting and designing cocrystal compositions, and the influence of structural intricacies on the final scintillation properties remain enigmatic. A comprehensive understanding of these scientific intricacies forms the pivotal cornerstone for the extension of this material system to X-ray scintillation applications.…”
Section: Doi: 101002/adom202302068mentioning
confidence: 99%
“…[35] Impressively, Tori Z. Forbes et al demonstrated that organic cocrystals could reduce structural defects when exposed to gamma radiation, especially in terms of maintaining crystallinity, stability, and physical properties, compared to polymers and single organic crystals. [36] However, the fundamental mechanism underlying the performance of organic cocrystals when exposed to radiation, the guiding principles for selecting and designing cocrystal compositions, and the influence of structural intricacies on the final scintillation properties remain enigmatic. A comprehensive understanding of these scientific intricacies forms the pivotal cornerstone for the extension of this material system to X-ray scintillation applications.…”
Section: Doi: 101002/adom202302068mentioning
confidence: 99%
“…In this study, we utilize experimental and computational approaches to examine the impact of γ radiation exposure on single‐component ( trans ‐stilbene, trans ‐1,2‐bis(4‐pyridyl)ethylene ( 4,4’‐bpe ), 1, n ‐diiodotetrafluorobenzene ( 1, n ‐C 6 I 2 F 4 ), 1, n ‐dibromotetrafluorobenzene ( 1, n ‐C 6 Br 2 F 4 ), 1, n ‐dihydroxybenzene ( 1, n ‐C 6 H 6 O 2 ) (where n =1, 2, or 3)) and as binary cocrystals ( 4,4’‐bpe ) ⋅ ( 1, n ‐C 6 I 2 F 4 ), ( 4,4’‐bpe ) ⋅ ( 1, n ‐C 6 Br 2 F 4 ), and ( 4,4’‐bpe ) ⋅ ( 1, n ‐C 6 H 6 O 2 ), where n =1, 2, or 3 (Scheme 1). These materials were chosen based on their similarity to common organic scintillators, aromaticity, and to introduce a variety of crystalline packing and halogen/hydrogen bonding arising from the systematic changes in functional group placement [16] . In this study, organic crystalline materials were exposed to a variety of γ radiation doses (0, 1, 5, 10, 20 kGy), then evaluated by electron paramagnetic resonance (EPR) spectroscopy before and after each irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Cocrystal engineering has previously been utilized for the rational design of materials for pharmaceutics, [14] optoelectronics, [15] and solid-state reactions, [8,9] and also can be used as a basis for the construction of radiation stable materials. [16] Using this tunability, atomistic-level changes in crystal packing and noncovalent interactions (i. e., hydrogen bonding, halogen bonding, π-π stacking) can be explored to relate structural integrity to γ radiation dose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations